PRIMARY AND SECONDARY PREVENTION OF CARDIOVASCULAR PATHOLOGY IN INJURED WITH COMBAT TRAUMA - Sydorova, N.M.; Druz, O.V.; Savytskyi, V.L.; Chernenko, I.A.; Sydorova, L.L. (World of Medicine and Biology, 2022)
The purpose of the study was to develop and implement measures for primary and secondary prevention of cardiovascular pathology in injured with combat trauma. The data of 448 injured with combat trauma who were admitted to the National Military Medical Clinical Center «Main Military Clinical Hospital» were analyzed. Analysis of the average values of biochemical blood parameters showed the presence among injured with combat trauma and signs of cardiovascular disease more pronounced metabolic disorders, cytolysis and inflammation compared with injured without such complication: high levels of fibrinogen (by 11.1 %, p=0.0294), glucose (by 11.1 %, p=0.0004), asparagine transaminase (by 74.6 %, p=0.0005), alanine transaminase (by 58.4 %, p=0.0013), and lower levels of total protein (by 7.1 %, p=0.0008). The obtained results allowed us to offer hypermetabolism syndrome as one of the mechanisms of cardiovascular pathology development in injured with combat trauma, as well as to develop and implement approaches for prevention of this syndrome associated with the secondary pathology of the cardiovascular system.